3-(5x+2)=2(4x-3)

Simple and best practice solution for 3-(5x+2)=2(4x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-(5x+2)=2(4x-3) equation:



3-(5x+2)=2(4x-3)
We move all terms to the left:
3-(5x+2)-(2(4x-3))=0
We get rid of parentheses
-5x-(2(4x-3))-2+3=0
We calculate terms in parentheses: -(2(4x-3)), so:
2(4x-3)
We multiply parentheses
8x-6
Back to the equation:
-(8x-6)
We add all the numbers together, and all the variables
-5x-(8x-6)+1=0
We get rid of parentheses
-5x-8x+6+1=0
We add all the numbers together, and all the variables
-13x+7=0
We move all terms containing x to the left, all other terms to the right
-13x=-7
x=-7/-13
x=7/13

See similar equations:

| 3n+12=9n+6 | | x²-7+10=0 | | 0.52x=7.8 | | 4x-2(x+3)=16 | | x^2+11x+30.25=23.25 | | 4x-2(x+3)=9 | | -5y+39=-7(y-7) | | 4x-2(x+3)=5 | | -22=-5x-2 | | 2.6x=1.5x+5.1 | | X+-8+x=55 | | 18+6x-12(2)=2x+10 | | 9x+7x+34=180 | | F(2)=1.8x=32 | | -9/10a-2=5 | | 2.5(-10+4x)=25 | | x3-3=40 | | F(1)=1.8x=32 | | -2(4-7x)=24x-8-10 | | 0.4(x+8)=16 | | 1/3k+800=1/2k+120 | | 5(y+1/3)=45 | | F(0)=1.8x=32 | | -(22-7t/41)=-1 | | u-4=22 | | 92=(3b+5) | | -0.8-1=3.2x+5 | | 105+30=x | | w÷ 5 = 34 | | 60w=90 | | -32-6x=53 | | -2y+21=-33 |

Equations solver categories